A case report of Cedecea davisae infection in a patient with chronic kidney disease in Saudi Arabia - Hani S. Al-Jahdali; Huda S. Al Ghamdi; Bothayna I. Saleh; Mohammed F. Merza; Bushra H. Alqurashy; Layali S. Abdurabo; Zahra A. Albishi; Rasha Binmahfouz (IDCases, 2025)
Cedecea, a genus belonging to the family Enterobacteriaceae, are uncommonly attributed as causative agents of human infections. Cedecea davisae is considered as an opportunistic pathogen that was isolated from a different acute infection in advanced-aged patients with many comorbid diseases or from immunocompromised hosts. Fourteen cases of proved C. davisae infections were published up till now. We isolated C. davisae from chronic kidney disease patient who presented with purulent discharge from dialysis catheter, and the result of microbiology culture and identification on automated microbiology identification system, MicroScan WalkAway using NBC50 panel revealed C. davisae as a causative agent of catheter related infection. The patient improved on receiving antibiotic treatment according to culture and sensitivity results. Awareness of the clinical significance of this low incidence bacterial infection and their antibiotic resistance and sensitivity pattern is crucial in the medical field.